Síntesis de catalizadores Ru-Ni soportados en γ- Al2 O3 para la hidrogenación de palmitato de metilo derivado del aceite de palma y conversión a alcohol cetílico - Rojas, Miguel (2018)
Catalysts based on Ru-Ni supported on γ-Al2O3 were prepared by the wet impregnation method with pH adjustment. The surface area of the supported catalysts was greater than that corresponding to the support with the adsorption isotherms corresponding to micromesoporous solids. The diffractograms of the reduced Ru-Ni catalysts were similar to that of the γ-Al2O3 support, suggesting the formation of highly dispersed phases. The TGA analysis revealed the mass loss of less than 20 % that would corroborate the transition of ruthenium and nickel hydroxides to their respective oxides. The reduction profiles of the Ru-Ni /γ-Al2O3 showed lower H2 consumption than those corresponding to Ru/ γ-Al2O3, revealing possible interactions between the metal phase and the support. In the hydrogenation of methyl palmitate, carried out under the operating conditions of a batch reactor, the activity was higher with the Ru /γ-Al2O3 catalyst with shorter reaction times, in comparison with Ru-Ni /γ-Al2O3. However, the selectivity to the formation of cetyl alcohol increased from 2.8 obtained with the Ru/ γ-Al2O3 only up to 12.5%, with the mixed catalyst Ru-Ni/γ-Al2O3 indicating the important influence of Ni on the formation of selective acidic sites in the hydrogenation of methyl palmitate in carbonyl position.